Influence of the Eurasian snow on the negative North Atlantic Oscillation in subseasonal forecasts of the cold winter 2009/2010 - Orsolini, Y; Senan, R; Vitart, F; Balsamo, G; Weisheimer, A; Doblas-Reyes, F (Springer, 2015)
The winter 2009/10 was remarkably cold and snowy over North America and across Eurasia, from Europe to the Far East, coinciding with a pronounced negative phase of the North Atlantic Oscillation (NAO). While previous studies have investigated the origin and persistence of this anomalously negative NAO phase, we have re-assessed the role that the Eurasian snowpack could have played in contributing to its maintenance. Many observational and model studies have indicated that the autumn Eurasian snow cover influences circulation patterns over high northern latitudes. To investigate that role, we have performed a suite of forecasts with the coupled ocean-atmosphere ensemble prediction system from the European Centre for MediumRange Weather Forecasts. Pairs of two-month ensemble forecasts with either realistic or else scrambled snow initial conditions are used to demonstrate how an anomalously thick snowpack leads to an initial cooling over the continental land masses of Eurasia and, within two weeks, to the anomalies that are characteristic of a negative NAO. It is also associated with enhanced vertical wave propagation into the stratosphere and deceleration of the polar night jet. The latter then exerts a downward influence into the troposphere maximizing in the North Atlantic region, which establishes itself within two weeks. We compare the forecasted NAO index in our simulations with those from several operational forecasts of the winter 2009/10 made at the ECWMF, and highlight the importance of relatively high horizontal resolution.